Highly Selective Bio-hydrocarbon Production using Sidoarjo Mud Based-Catalysts in the Hydrocracking of Waste Palm Cooking Oil - Wega Trisunaryanti; Triyono Triyono; Iip Izul Fallah; Shafira Salsiah; Gesha Desy Alisha (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
In this work, Lapindo mud (LM) was used as catalyst support. This is because the Lapindo mud has a high SiO2 content of 45.33 %. This research aims to produce a hydrocracking catalyst based on Lapindo mud through impregnation of Ni and Pt metals as well as grafting amine groups. Ni and Pt metals impregnation using wet impregnation method followed by amine group grafting. The best catalyst in this study was NiPt-NH2/LM which contained Ni and Pt metals, surface area, and pore diameters of 1.68 wt.% and 0.4 wt.%, 6.59 m2/g, 15.51 nm, respectively. The effectiveness of the catalyst was tested against temperature and catalyst: feed ratio. The catalyst with the best activity and selectivity was tested for reusability 3 times through hydrocracking process. The yield of liquid products obtained in the hydrocracking process of WPO using NiPt-NH2/LM catalyst with the optimum temperature and the weight ratio of catalyst:feed at 550 oC was 79.4 wt. % which consists of hydrocarbon compound of 55.9 wt.%. The yield of liquid products obtained in the hydrocracking WPO using the used NiPt-BH2/LM catalyst was 28.4 wt.% which consists of hydrocarbon compound of 23.6 wt.%. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).